KAJIAN PENGEMBANGAN KOMODITAS TANAMAN NANAS (Ananas Comosus) DI KABUPATEN MUARO JAMBI - Nuraini, Riska Ayu; Ahyuni, Ahyuni (JURNAL BUANA, 2025)
This research was conducted in Muaro Jambi District and aims to determine the suitability of pineapple plantations and the directions for their development. This type of research is quantitative, and the data used is secondary data with data processing using fuzzy logic and boolean logic methods. The results of this study indicate that the suitability of unsuitable class pineapple plantation land is 147,813 ha, with a percentage of 27.76 percent. For the quite suitable class, the area is 138,598 ha with a percentage of 26.03 percent, and the very suitable class covers an area of 262,490 ha with a percentage of 49.22 percent. As well as development directions that are not suitable for pineapple covering an area of 159.858 ha include the districts of Kumpeh, Sungai Gelam,Maro Sebo, and Taman Rajo. For appropriate development directions, it has an area of 371.756 ha, predominantly located in Mestong District 44,297 ha and Kumpeh District 129,979 ha, Sekernan District 59,393 ha, Bahar Utara District 17,569 ha, Bahar Selatan District 17,695 ha, Sungai Bahar District 15,802 ha and Jambi Outer City District 25,762 ha.